Cannabis use and stressful life events during the perinatal period: cross‐sectional results from Pregnancy Risk Assessment Monitoring System (PRAMS) data, 2016. (10th March 2020) - Allen, Alicia M.; Jung, Alesia M.; Alexander, Adam C.; Allen, Sharon S.; Ward, Kenneth D.; al'Absi, Mustafa
Abstract: Aims: We aimed to determine the association between stressful life events (SLEs) in the year prior to childbirth with (1) pre‐pregnancy cannabis use, (2) cessation of cannabis use during pregnancy and (3) postpartum relapse to cannabis use. Design: We used data from the Pregnancy Risk Assessment Monitoring System (PRAMS) 2016, a cross‐sectional, population‐based surveillance system. Setting: Mailed and telephone surveys conducted in five states—Alaska, Colorado, Maine, Michigan and Washington—in the United States. Participants: Women ( n  = 6061) who delivered a live infant within the last 6 months and had data on cannabis use. Measurements: Self‐reported data included SLEs (yes/no response for 14 individual events in the 12 months prior to childbirth) and cannabis use [yes/no prior to pregnancy, during pregnancy, and at the time of the survey (approximately 2–6 months postpartum)]. The associations between SLEs and cannabis use (primary outcomes) were examined in logistic regression models adjusted for maternal demographics (e.g. age, race, education), geography (i.e. state of residence) and cigarette smoking. Findings: Pre‐pregnancy, 16.4% (997/6061) of respondents endorsed using cannabis, with 36.4% (363/997) continuing cannabis use during pregnancy. Among the 63.6% (634/997) who did not report use during pregnancy, 23.2% (147/634) relapsed to cannabis use during the postpartum. Nine of the 14 possible SLEs were associated with increased odds of pre‐pregnancy cannabis use [e.g. husband/partner or mother went to jail, adjusted odds ratio (aOR) = 2.16, 95% confidence interval (CI) = 1.30–3.62] and four were associated with increased odds of continued cannabis use during pregnancy (e.g. husband/partner lost job, aOR = 2.19, 95% CI = 1.21–3.96). The odds of postpartum relapse to cannabis were significantly associated with two SLEs (husband/partner said they did not want pregnancy, aOR = 2.86, CI = 1.10–7.72; husband/partner or mother went to jail, aOR = 0.37, 95% CI = 0.13–1.00). Conclusions: Stressful life events during the year prior to childbirth appear to be linked to greater odds of women's cannabis use during the perinatal period, especially during pre‐pregnancy.